Evaluation of self-absorption of manganese emission lines in Laser Induced Breakdown Spectroscopy measurements - Bredice, Fausto Osvaldo (2006)
This paper is part of a more general study aimed to the determination of the best experimental procedures for reliable quantitative measurements of Fe-Mn alloys by LIBS. In this work, attention is pointed on the self-absorption processes, whose effect deeply influences the LIBS measurements, reflecting in non-linear calibration curves. The effect of self-absorption on the line intensity can be quantified by defining a self absorption coefficient, that measures the deviation of the line intensity from the linear extrapolation of the curve of growth in the optically thin regime. The authors demonstrated in a previous paper that self absorption coefficients could be calculated once the electron density of the plasma is known and the Stark coefficients of the lines are available. However, when the Stark coefficients of the lines of interest are not known, a different approach is needed. In this work a new method for evaluation of self absorption coefficients in LIBS measurements is presented, which does not require the knowledge of Stark coefficients. In order to understand the basic principles and setting out the theoretical tools that will be used for the analysis o f the alloys, a preliminary study was done on pure Mn; LIBS spectra were acquired in different experimental conditions, at different laser energies and different delays after the laser irradiation o f the sample. Moreover, collinear double pulse measurements were also performed. Analytical relations were derived and experimental procedures devised for evaluation o f the self absorption coefficients of several Mn lines, which are important for characterization and control of the experimental conditions in which the analysis is performed.